2021
DOI: 10.1111/jcpp.13549
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risks for joint developmental trajectories of internalizing and externalizing problems: findings from the ALSPAC cohort

Abstract: Background Joint developmental trajectories of internalizing and externalizing problems show considerable heterogeneity; however, this can be parsed into a small number of meaningful subgroups. Doing so offered insights into risk factors that lead to different patterns of internalizing/externalizing trajectories. However, despite both domains of problems showing strong heritability, no study has yet considered genetic risks as predictors of joint internalizing/externalizing problem trajectories. Methods Using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
5
18
0
Order By: Relevance
“…These findings are in line with previous research highlighting that most mental health problems share common aetiological factors that mostly reflect between-person differences (Caspi & Moffitt, 2018). For instance, polygenic risk scores for ADHD have been found to be associated with both internalising and externalising difficulties, as have a variety of other risk factors such as maternal history of depression or smoking during pregnancy (Murray et al, 2020b;Speyer et al, 2021). With regards to interventions, this suggests that in addition to focusing on targeting pathways that potentially increase the likelihood of someone suffering from one mental health problem to develop another mental health problem, it is highly important to identify those individuals most at risk for developing co-occurring mental health problems based on the broader set of risk factors an individual presents with.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with previous research highlighting that most mental health problems share common aetiological factors that mostly reflect between-person differences (Caspi & Moffitt, 2018). For instance, polygenic risk scores for ADHD have been found to be associated with both internalising and externalising difficulties, as have a variety of other risk factors such as maternal history of depression or smoking during pregnancy (Murray et al, 2020b;Speyer et al, 2021). With regards to interventions, this suggests that in addition to focusing on targeting pathways that potentially increase the likelihood of someone suffering from one mental health problem to develop another mental health problem, it is highly important to identify those individuals most at risk for developing co-occurring mental health problems based on the broader set of risk factors an individual presents with.…”
Section: Discussionsupporting
confidence: 91%
“…Using the "unaffected" class as the reference class, they found that male sex/gender increased the likelihood of membership in several classes characterized by elevations of symptoms in all three domains but not in a class characterized only by elevations in internalizing problems. Speyer et al (2021) found that male sex increased the likelihood of membership in age 4-16 trajectory classes characterized by high internalizing and externalizing symptoms; moderate externalizing symptoms; and high externalizing symptoms compared to the unaffected class. However, male sex did not increase the likelihood of membership in their class characterized by moderate internalizing and externalizing levels.…”
Section: Introductionmentioning
confidence: 92%
“…Given that secondary symptoms may interact with and/or modify primary symptoms (Drabick & Kendall, 2010), examination of sex/gender differences in joint trajectories of symptoms is important. There have, however, only been a handful of studies examining sex/gender differences in co‐occurring mental health issue trajectories covering the adolescent period (Chen & Simons‐Morton, 2009; Diamantopoulou et al., 2011; Patalay et al., 2017; Speyer et al., 2021). One study examined joint developmental trajectories of ADHD, internalizing, and externalizing symptoms across ages 7–15 (Murray et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using methods such as latent class growth models (or parallel-process LCGA), ample evidence has also indicated the substantial between-family heterogeneity in the (co-) development of youth internalizing and externalizing problems. Identified trajectory groups have included, for example, pure and co-occurring internalizing and/or externalizing problems at high or moderate levels (or with some changes when transitioning to adolescence) and low symptoms (Murray et al, 2020;Patalay et al, 2017;Speyer et al, 2021). Given that previous studies differ considerably in design, analytical strategy, and age span, these findings have themselves been highly heterogeneous in terms of the specific trajectory groups that have emerged.…”
mentioning
confidence: 99%